Cloning and characterization of polyhydroxyalkanoate (PHA) genes from Pseudomonas sp. isolated from Antarctica - Yit, Le Yau; Abdullah, Amirul AI-Ashraf; Kumar, Sudesh; Samian, Mohd Razip; Najimudin, Nazalan (Penerbit Universiti Sains Malaysia, 2004)
Pseudomonas strains accumulate mediumchain-length poly(R)-3-hydroxyalkanoate (PHA) as carbon and energy source under conditions of limiting nutrients in the presence of an excess of carbon source (Fidler et al., 1992).